Quantitative projection of human brain penetration of the H3 antagonist PF-03654746 by integrating rat-derived brain partitioning and PET receptor occupancy. (1st February 2017) - Sawant-Basak, Aarti; Chen, Laigao; Shaffer, Christopher L.; Palumbo, Donna; Schmidt, Anne; Tseng, Elaine; Spracklin, Douglas K.; Gallezot, Jean-Dominique; Labaree, David; Nabulsi, Nabeel; Huang, Yiyun; Carson, Richard E.; et al.
Abstract: 1. Unbound brain drug concentration ( C b, u ), a valid surrogate of interstitial fluid drug concentration ( C ISF ), cannot be directly determined in humans, which limits accurately defining the human C b, u : C p, u of investigational molecules. 2. For the H3 R antagonist (1 R, 3 R )- N -ethyl-3-fluoro-3-[3-fluoro-4-(pyrrolidin-1-lmethyl)phenyl]cyclobutane-1-carboxamide (PF-03654746 ), we interrogated C b, u : C p, u in humans and nonhuman primate (NHP). 3. In rat, PF-03654746 achieved net blood–brain barrier (BBB) equilibrium ( C b, u : C p, u of 2.11). 4. In NHP and humans, the PET receptor occupancy-based C p, u IC50 ofPF-03654746 was 0.99 nM and 0.31 nM, respectively, which were 2.1- and 7.4-fold lower than its in vitro human H3 K i (2.3 nM). 5. In an attempt to understand this higher-than-expected potency in humans and NHP, rat-derived C b, u : C p, u ofPF-03654746 was integrated with C p, u IC50 to identify unbound (neuro) potency ofPF-03654746, n IC50 . 6. The n IC50 ofPF-03654746 was 2.1 nM in NHP and 0.66 nM in human which better correlated (1.1- and 3.49-fold lower) with in vitro human H3 K i (2.3 nM). 7. This correlation of the n IC50 and in vitro h H3 K i suggested the translation of net BBB equilibrium ofPF-03654746 from rat to NHP and humans, and confirmed the use of C p, u as a reliable surrogate of C b, u . 8. Thus, n IC50 quantitatively informed the human C b, u : C p, u ofPF-03654746 .